Factors associated with the Incidence of Occupational Contact Dermatitis of the Hands among Cleaning Service Workers - Salwa Azzahra; Akhyar, Gardenia; Satya Wydya Yenny; Raveinal; Ida Rahmah Burhan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Occupational contact dermatitis (OCD) is one of the most common occupational diseases worldwide. Occupational diseases in hospitals can affect all workers, including both medical and non-medical personnel, such as cleaning service workers. Purpose: This study aims to determine the factors associated with the incidence of OCD of the hands among cleaning service workers at Dr. M. Djamil Central General Hospital Padang. Methods: This study is an observational analytic study with a cross-sectional design. The sampling technique used was consecutive sampling with 77 total samples. The data were collected by direct interview with a questionnaire instrument. Data analysis used univariate and bivariate analysis with a chi-square test. Result: The results revealed that 28 out of 77 respondents experienced OCD (36.4%). The results of the chi-square test show that the factors of gender (p=0.000) and the use of moisturizers (p=0.017) had a significant relationship with the incidence of OCD. Meanwhile, the factors of age (p=0.725), working period (p=0.492), duration of contact (p=0.862), history of skin diseases (p=0.176), history of atopy (p=0.421), duration of PPE use (p=0.119) did not have a significant relationship with the incidence of OCD. Conclusion: The study concludes that the incidence of OCD of the hands among cleaning service workers at Dr. M. Djamil Central General Hospital Padang is correlated with their gender and their use of moisturizers.